Epigenomic Blood-Based Early Detection of Pancreatic Cancer Employing Cell-Free DNA - Haan, David; Bergamaschi, Anna; Friedl, Verena; Guler, Gulfem D.; Ning, Yuhong; Reggiardo, Roman; Kesling, Michael; Collins, Micah; Gibb, Bill; Hazen, Kyle; Bates, Steve; Antoine, Michael; et al. (Clinical gastroenterology and hepatology, 2023)
Early detection of pancreatic cancer (PaC) can drastically improve survival rates. Approximately 25% of subjects with PaC have type 2 diabetes diagnosed within 3 years prior to the PaC diagnosis, suggesting that subjects with type 2 diabetes are at high risk of occult PaC. We have developed an early-detection PaC test, based on changes in 5-hydroxymethylcytosine (5hmC) signals in cell-free DNA from plasma. Blood was collected from 132 subjects with PaC and 528 noncancer subjects to generate epigenomic and genomic feature sets yielding a predictive PaC signal algorithm. The algorithm was validated in a blinded cohort composed of 102 subjects with PaC, 2048 noncancer subjects, and 1524 subjects with non-PaCs. 5hmC differential profiling and additional genomic features enabled the development of a machine learning algorithm capable of distinguishing subjects with PaC from noncancer subjects with high specificity and sensitivity. The algorithm was validated with a sensitivity for early-stage (stage I/II) PaC of 68.3% (95% confidence interval [CI], 51.9%–81.9%) and an overall specificity of 96.9% (95% CI, 96.1%–97.7%). The PaC detection test showed robust early-stage detection of PaC signal in the studied cohorts with varying type 2 diabetes status. This assay merits further clinical validation for the early detection of PaC in high-risk individuals. [Display omitted]